2016
DOI: 10.3892/ol.2016.4584
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 Gln11Leu single nucleotide polymorphism and susceptibility to cutaneous melanoma

Abstract: Abstract. Cutaneous melanoma is a life-threatening skin cancer. Its incidence is rapidly increasing, and early diagnosis is the main factor able to improve its poor prognosis. Toll-like receptors (TLRs) are transmembrane glycoproteins that recognize pathogen-and damage-associated molecular patterns, against which TLRs activate the innate immune response and initiate the adaptive immune response. Genetic variations of these receptors may alter the immune system, and are involved in evolution and susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…In our study, the prevalence of TLR7 rs179008 AA, AT, and TT genotypes in healthy controls was 81.0%, 16.5%, and 2.5%. This finding was unmatched with that of the other studies carried out by [12,13,29,14]. The occurrence of TLR7 rs179008A/T allelic frequency was comparable with the study carried out by Valverde-Villegas et al, 2017, [30,6,16] and dissimilar with the study reported by [6,12,13,29].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In our study, the prevalence of TLR7 rs179008 AA, AT, and TT genotypes in healthy controls was 81.0%, 16.5%, and 2.5%. This finding was unmatched with that of the other studies carried out by [12,13,29,14]. The occurrence of TLR7 rs179008A/T allelic frequency was comparable with the study carried out by Valverde-Villegas et al, 2017, [30,6,16] and dissimilar with the study reported by [6,12,13,29].…”
Section: Discussionsupporting
confidence: 80%
“…We had observed a nonsignificant distribution of TLR7 rs179008 polymorphism between HIV-infected individuals and healthy controls, although TLR7 rs179008AT genotype was much more prevalent in HIV-infected individuals as While as an association was seen between TLR7 rs179009AG genotype and acquisition of HIV-1 (OR = 0:42, P = 0:016), TLR7rs179008A/T polymorphism was associated with susceptibility to asthma [17], course of hepatitis C infection [12], HIV-1 acquisition, and disease progression [6]. TLR7 rs179008 polymorphism was not associated with patients of basal cell carcinoma (BCC) [12], melanoma cases (P = 0:245), and between single melanoma and MPM cases (P = 0:482) [14]. TLR7 IVS2-151G/A allele was associated with the protection of female patients of chronic hepatitis C (P ≤ 0:001, OR =0.46) [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosomal aberrations or nucleotide polymorphisms affect pathways involved in tumor formation and progression in breast cancer or cutaneous melanoma ( 37 , 38 ). However, the present study was unable to identify chromosomal alterations and detected only a few nucleotide variations in m Cyld −/− compared with m Cyld +/+ cells.…”
Section: Discussionmentioning
confidence: 99%
“…ln11Leu polymorphism and susceptibility to develop melanoma was found. Further, other studies on TLR polymorphisms and their susceptibility to malignant melanoma are needed [131].…”
Section: Melanomamentioning
confidence: 99%